Understanding the Relationship Between Gender Representation in County Government and Perinatal Outcomes to Black, White, and Hispanic Birthing People in Georgia - Kaitlyn K. Stanhope; Pragati Kapila; Afsha Hossain; Maha Abu-Salah; Vanshika Singisetti; Amal Umerani; Sierra Carter; Sheree Boulet (Mary Ann Liebert, 2024)
Objective: To characterize the association between percent of county-level elected officials who were female-presenting and perinatal outcomes in Georgia and variation by individual race, 2020?2021. Materials and Methods: We gathered data on the gender composition of county-level elected officials for all Georgia counties (n?=?159) in 2022 and calculated the percent of female elected officials (percent female, 0?100). We linked this to data from 2020 to 2021 birth certificates (n?=?238,795) to identify preterm birth (PTB, <37 weeks), low birthweight (LBW, <2500 grams), hypertensive disorders of pregnancy, and cesarean delivery. We fit multilevel log binomial models with generalized estimating equations, with percent female as the primary independent variable. We adjusted for individual and county-level potential confounders and individual race/ethnicity as an effect modifier. Results: County median percent female elected officials was 22.2% (interquartile range: 15.5). Overall, 14.6% of births were PTB and 10.1% LBW. A 15 percentage point increase in percent female elected officials was associated with lower risk of hypertensive disorders of pregnancy for white (adjusted risk ratio [RR]: 0.94, 95% confidence interval [CI]: 0.88?0.99), and possibly Hispanic (adjusted RR: 0.95, 95% CI: 0.89?1.0) and non-Hispanic other (adjusted RR: 0.94 (0.87?1.01), but not black birthing people (adjusted RR: 1.0, 95% CI: 0.95?1.05). There was not a clear pattern for PTB, birthweight, or cesarean delivery. Conclusion: Greater female representation in county government was associated with improved maternal health for some racial/ethnic groups in Georgia.